Perancangan Simulator Differential Konvensional Menggunakan Penggerak Motor Listrik - Abdul Muis; Abdul Halik; Mangkona Mangkona; Abdul Halim; Hidayat Hidayat (Politeknik Negeri Samarinda, 2021)
Design and manufacture of this simulator aims to explain how the movement of the differential components. The components of this differential simulation consist of a differential case, pinion gear or spider gear, side gear, spider shaft, electric motor, pulley, v-belt and dimmer (motor speed controller). The method used in making this simulator is to start by first making a simulator design and then continuing with the collection of tools and materials needed. From testing the components of the simulator tool which was carried out for 50 minutes, it was found that every 10 minutes the temperature increased due to the lubrication system that was not maximized. Tests to determine the correlation between the dimmer and the RPM of the electric motor, it was found that any decrease in the resistance value will result in an increase in the RPM value of the electric motor. These results also show that the maximum value of the motor RPM after being assembled is 1435 RPM. Then the test when given a load found that the shaft axle rotation speed of the differential will change if there is a load on one side. From this test, it can be seen that there is an increase in the RPM value on the side of the shaft axle which rotates freely when the other shaft is given a load. With this simulator, it can also provide an overview of how the movement of the differential gears contained in the axle of a unit vehicle so that you can understand how it works